KEMAMPUAN MENULIS MAKALAH MAHASISWA DI PROGRAM STUDI PENDIDIKAN FISIKA UNIVERSITAS KH. A. WAHAB HASBULLAH. - asiyah lu’lu’ul husna (JoEMS (Journal of Education and Management Studies), 2020)
This study aims to determine the ability to write papers by students of physics education courses at the University of KH. A. Wahab Hasbullah. Research subjects were students of physics education at the Faculty of Education, Kh University. A. Wahab Hasbullah in semester 1 of the 2019/2020 school year as many as 30 people. This research uses descriptive quantitative research design because the research objective is to determine the ability to write papers in terms of aspects of the characteristics of the paper, aspects of the structure of the paper and aspects of language use. The data collection techniques by reading the entire paper made by students, the aim is to identify and measure the level of scholarship consisting of the contents of the paper, organization of papers, vocabulary and terms, use of language, and spelling and writing techniques. The conclusion of this study is the ability to write scientific papers (papers) students viewed from aspects of the characteristics of papers by 65% ​​with a fairly good category, the ability to write scientific papers (papers) students viewed from the aspect of the structure of papers by 65% ​​with a fairly good category and ability writing scientific papers (papers) students viewed from the aspect of linguistic use by 63% with quite good category